A new and efficient synthesis of (3E,8Z,11Z)-tetradeca-3,8,11-trienyl acetate, the major sex pheromone component of the tomato leafminer Tuta absoluta - Cabezas Pizarro, Jorge A. (2018)
An efficient synthesis of (3E,8Z,11Z)-tetradeca-3,8,11-trienyl acetate, the major sex pheromone component of the tomato leafminer moth, Tuta absoluta, was accomplished. The synthesis started with but-3-yn-1-ol and gave an overall yield of 41%.